Rabbi - Pastor - Priest : Their Roles and Profiles through the Ages - Homolka, Walter; Schöttler, Heinz-Günther, 1950- (Studia Judaica (Walter de Gruyter & Co.) ;, 2013)
Both Judaism and Christianity have authorized clergy, charged with fulfilling a multitude of tasks in their respective communities. They teach, provide pastoral care, and preach. They lead worship, hold services and offer counseling regarding all aspects of life. They perform religious rites at the beginning and end of life as well as in-between. They make decisions regarding religious questions, serve as administrators, and possibly even mediate?between heaven and earth'. The concrete forms of realization and the functions of the office are not only defined through theological specification.